PENGARUH KOMPETENSI DAN PEMBERIAN PENGHARGAAN TERHADAP SEMANGAT KERJA KARYAWAN PT. DEWA RENCANA KABUPATEN LANGKAT - Supriadi Siagian (Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
Employee work spirit must be considered, because work spirit is a person's desire and sincerity in doing their job well and discipline to achieve maximum work performance. The purpose of this study was to see the effect of competence and reward on employee work spirit at PT. Dewa Rencana, Langkat Regency. PT. Dewa Rencana Langkat is a company engaged in palm oil processing. The phenomenon that occurs in the company is a decrease in employee work spirit. One of the things that causes a decrease in employee work spirit is competence and reward. The company does not place employees according to their competence, as a result employees often find it difficult to understand their work. The company does not have a good reward system. The population in this study were all employees in the company totaling 30 people. The sample was taken using a saturated sampling technique where all members of the population were used as samples. Thus, the sample in this study amounted to 30 people. The results of the simultaneous hypothesis test showed that simultaneously the competency and reward variables had a significant effect on employee work spirit at PT. Dewa Rencana. Partially, each competency and reward variable had a significant effect on employee work spirit at PT. Dewa Rencana